Simulation of a suspension system with adaptive fuzzy active force control - Mailah, M.; Priyandoko, G. (DAAAM International, Vienna, 2007)
This paper presents the design of a new and novel control technique applied to an active suspension system of a quarter car model using adaptive fuzzy (AF) logic and active force control (AFC) strategies. The two main advantages of the proposed method are the simplicity of the control law and low computational burden. The overall control system essentially comprises three feedback control loops, namely the innermost PI control loop for the force tracking of the hydraulic actuator, intermediate AFC control loops for the compensation of the disturbances and outermost AF control loop for the computation of the optimum target/commanded force. AF algorithms were used to approximate the estimated mass of the hydraulic actuator in the AFC loop. The performance of the proposed control method was then simulated, evaluated and later compared to examine the effectiveness of the system in suppressing the undesirable effects of the suspension system. It was found that the active suspension system with Adaptive Fuzzy Active Force Control (AF-AFC) yields superior performance compared to the AF system without AFC and the passive counterparts.